PENINGKATAN PENERAPAN CONTEXTUAL TEACHING AND LEARNING MELALUI STRATEGI PEMODELAN DAN PEMBERIAN TUGAS SEBAGAI TINDAK LANJUT SUPERVISI AKADEMIK - ., Abdulah (Jurnal Visi Ilmu Pendidikan, 2014)
Abdulah.2011.The improvement of Contextual Teaching and Learning Application  through Task and Model Strategy as the Sustainable Academic Supervision The study is based on the weakneses of Bahasa Indonesia teacher  of SMP Negeri 4 Sungai Ambawang in appliying  of the Contextual Teaching and Learning Approach on Bahasa Indoneaia subject. The CTL approach is intended to make the atmosphere of learning teaching proses enjoyable for the students. The issues of is study is how well  the plan, the action and the evaluation conducted to improve the Contextual Teaching and Learning application through Task and Model Strategy as the sustainable of Academic Supervision of SMP Negeri 4 Sungai Ambawang. Academic Supervision of SMP Negeri 4 Sungai Ambawang. Academic Year 2010-2011. The study designed is the school Action Reaseach, by descriptive mettod and qualitative  study form. The students and  a teacher are data source, the data shows in this study as the competence of the teacher to make plan, do the action and the students activities in the learning teaching process. The data collecting is observation sheet and interview and teacher performance evaluation in which the seven components of CTL The result of the study shows that the applaying of CTL approach through Task and Model Strategy as the sustainable Academic Supervision on guru Bahasa Indonesia of SMP Negeri 4 Sungai Ambawang Kabupaten Kubu Raya Academic Year 2010-2011 improve the teachers competence in planning action and action and the students result in learning effectively.   Keyword: CTL,approach, task and model, academic supervision